Synthetic Cationic Peptide IDR-1002 and Human Cathelicidin LL37 Modulate the Cell Innate Response but Differentially Impact PRRSV Replication in vitro - Levast, Benoît; Hogan, Daniel; van Kessel, Jill; Strom, Stacy; Walker, Stew; Zhu, Jianzhong; Meurens, François; Gerdts, Volker (Frontiers in Veterinary Science, 2019)
Host defense peptides (HDPs) show both antimicrobial and immunomodulatory properties making them important mediators of the host immune system. In humans but also in pigs many HDPs have been identified and important families such as cathelicidins and defensins have been established. In our study, we assessed: i) the potential interactions that could occur between three peptides (LL37, PR39, and synthetic innate defense regulator (IDR)-1002) and a common TLR ligand called poly(I:C); ii) the impact of selected peptides on the response of alveolar macrophage (AM) to poly(I:C) stimulation; iii) the anti-porcine respiratory and reproductive syndrome virus (PRRSV) properties of the peptides; and iv) their adjuvant potential in a PRRSV challenge experiment after immunization with different vaccine formulations. The results are as following: LL37, PR39, and IDR-1002 were able to interact with poly(I:C) using an agarose gel migration assay. Then, an alteration of AM’s response to poly(I:C) stimulation was observed when the cells were co-stimulated with LL37 and IDR-1002. Regarding the anti-PRRSV potential of the peptides only LL37 showed a PRRSV inhibition in infected AM as well as precision cut lung slices (PCLS). However, in our conditions and despite their immunomodulatory properties, neither LL37 nor IDR-1002 showed any convincing potential as an adjuvant when associated to killed PRRSV in a challenge experiment. In conclusion, both antiviral and immunomodulatory properties could be identified for LL37, only immunomodulatory properties for IDR-1002, and both peptides failed to improve the immune response consecutive to an immunization with a killed vaccine in a PPRSV challenge experiment. However, further studies are needed to fully decipher and explain differences between peptide properties.